Growth and Production Response of Corn (Zea mays L.) by Bokashi of Cow Waste and Tempe Industrial Liquid Waste - Barus, Wan Arfiani; Utami , Sri; Tanjung, Dicky Zulkarnain (Talenta Publisher, 2019)
The study aims to investigate the response of growth and production of the corn plant (Zea mays L.) due to the provision of bokashi cow dung and Tempe industrial liquid waste. This study was conducted in February 2017 until June 2017 at Lahan Perkebunan Rakyat Jalan Manunggal Ujung, Desa Bandar Klippa, Kecamatan Percut Sei Tuan, Medan Tembung. The design used was Factorial Randomized Block Design (RBD) with 3 replications and consisted of two factors studied: Bokashi consisting of four levels, e.i : B0 : Control, B1 : 15 ton/ha, B2 : 30 ton/ha and B3 : 45 ton/ha. The use of industrial liquid waste Tempe consisting of four levels, namely, e.i: L0 : Control, L1 : 30 ml/l, L2 : 60 ml / l, L3 : 90 ml/l. The observation data was followed by Duncan Multiple Range Test (DMRT). The results showed that the use of bokashi cow dung had a significant effect on the observation parameters of height, leaf length and cob weight in corn plants that have been observed and not significant to the observation of leaf number, leaf area, dry seed weight each plot. The use of industrial effluent of Tempe has a significant effect on leaf length parameter at age 6 weeks after planting and cob weight/plant each plot but not significant effect on observation of plant height, leaf number, leaf area, dry seed weight each plot.